“The World Economy of Coronavirus”: Search for Optimal Ways to Overcome the Consequences of the Crisis - E. N. Smirnov (Vestnik MGIMO-Universiteta)
The current pandemic of COVID-19 has already become a test of strength for world economy and institutions of global economic regulation. The main goal of the article is to review existing research on the economy of pandemics focusing on COVID-19, and to develop a conceptual framework for further assessment of negative impact of COVID-19 on the economies of the world and ways to minimize this impact on economic development. The author’s methodological approach goes beyond the traditional interpretation of the pandemic economy; we use the term “coronavirus global economy” to show the unprecedented and comprehensive impact of a pandemic on the development of the world economy, the movement of factors of production, economic integration and economic growth. Under these conditions, many theories of economic development, the mechanisms of trade and investment policies need to be seriously reevaluated. The review shows that the increasing negative impact of COVID-19 on the global economy lies in the fact that it has not managed to recover from the global crisis of 2008 and was in a "pre-recession" state; the preparedness of countries to counter the pandemic was extremely low, and the institutions of international cooperation were paralyzed failing to develop measures to effectively protect against the current consequences of COVID-19. The review of the literature demonstrates the uniqueness of the current pandemic in terms of negative effects on both the supply and demand side of the global financial system, which is especially aggravated by the high debt burden of many countries. Globalization is considered to be the main determinant of the high spread of the coronavirus pandemic in both the medical and economic contexts, but at the same time, states remain fragmented and protectionist in terms of combating the pandemic.